2016
DOI: 10.1080/03078698.2016.1197698
|View full text |Cite
|
Sign up to set email alerts
|

Results from the first GPS tracking of roof-nesting Herring GullsLarus argentatusin the UK

Abstract: Recent developments in GPS tracking technology are allowing the movements of bird species to be followed in ever greater detail. Seabird research is benefiting greatly due to the challenges of tracking species that often roam widely out at sea. Amongst the gulls, one of the pressing issues is to understand the ecology of the relatively recent urban colonists and how they differ from their counterparts in traditional rural colonies. Here, we present what we believe are the first GPS results from roof-nesting gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
2
25
0
5
Order By: Relevance
“…Within‐colony variation in individual movement patterns was recently demonstrated for roof‐nesting herring gulls, based on GPS data (Rock et al, 2016). A multi‐colony approach, based on pellets and stable isotope data of chicks, showed that the breeding success of herring gulls in Scotland depended on the foraging habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Within‐colony variation in individual movement patterns was recently demonstrated for roof‐nesting herring gulls, based on GPS data (Rock et al, 2016). A multi‐colony approach, based on pellets and stable isotope data of chicks, showed that the breeding success of herring gulls in Scotland depended on the foraging habitat.…”
Section: Introductionmentioning
confidence: 99%
“…They efficiently adapt to exploiting a wide suite of novel resources that provide direct biotic and abiotic benefits, including food, shelter and refuge from predation (Ramírez et al 2012, Alonso et al 2015, Osterback et al 2015. These winning seabirds are often perceived as pests because of their impacts on urban areas, water reservoirs and threatened species (Vidal et al 1998, Skórka et al 2014, Rock et al 2016. As a consequence, abundant research has been conducted on these opportunistic predators, mainly focused on their population dynamics, feeding ecology, pollution levels and pathogen load (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1) abarca, en términos globales, (1) la franja de costa desde la colonia de Ulía hasta el punto de alimentación en el vertedero de Zaluaga en Senpere, (2) otra franja de territorio a lo largo de un eje que une la colonia con el vertedero de Sasieta en Beasain (con una nube de puntos densa en zonas de prados y paisaje de campiña en la zona baja de la cuenca del Urumea así como en la cuenca del río Oria, particularmente en el Asteasu), (3) un área marina de unos 1500 km 2 frente a la colonia. En promedio, la superficie (polí-gono mínimo convexo) (Bosch et al, 2009;Rock et al, 2016) abarcada por cada ejemplar fue de 911,34 km 2 (SE = 425,74 km 2 ; rango: 307,75-2158,10 km 2 ; Tabla 1; Fig. 2).…”
Section: Resultsunclassified
“…Nuestros resultados son consistentes con otros estudios sobre ecología espacial en gaviotas (Bouten et al, 2013;Tyson et al, 2015;Rock et al, 2016). Los resultados mostrados en este Tabla 2.-Porcentaje de localizaciones nocturnas y diurnas según hábitat, durante el periodo de reproducción (meses de junio y julio), de 4 ejemplares adultos de gaviota patiamarilla marcados en la colonia de Ulía (Donostia).…”
Section: Discussionunclassified
See 1 more Smart Citation